The central role of DNA damage and repair in CAG repeat diseases - Massey, Thomas H. (Dis Model Mech, 2018)
Diseases such as Huntington's disease and certain spinocerebellar ataxias are caused by the expansion of genomic cytosine-adenine-guanine (CAG) trinucleotide repeats beyond a specific threshold. These diseases are all characterised by neurological symptoms and central neurodegeneration, but our understanding of how expanded repeats drive neuronal loss is incomplete. Recent human genetic evidence implicates DNA repair pathways, especially mismatch repair, in modifying the onset and progression of CAG repeat diseases. Repair pathways might operate directly on repeat sequences by licensing or inhibiting repeat expansion in neurons. Alternatively, or in addition, because many of the genes containing pathogenic CAG repeats encode proteins that themselves have roles in the DNA damage response, it is possible that repeat expansions impair specific DNA repair pathways. DNA damage could then accrue in neurons, leading to further expansion at repeat loci, thus setting up a vicious cycle of pathology. In this review, we consider DNA damage and repair pathways in postmitotic neurons in the context of disease-causing CAG repeats. Investigating and understanding these pathways, which are clearly relevant in promoting and ameliorating disease in humans, is a research priority, as they are known to modify disease and therefore constitute prevalidated drug targets.